Dances with potential food waste: Organising temporality in food waste reduction practices. (November 2019) - Mattila, Malla; Mesiranta, Nina; Närvänen, Elina; Koskinen, Outi; Sutinen, Ulla-Maija
This study describes and analyses how practices organise temporality to reduce food waste. The study builds upon the material turn in practice theories and an ontological approach that together highlight emerging relations between humans and non-humans in practices. Three theoretical propositions are constructed that inform the empirical analysis. The study utilises empirical qualitative data from a Finnish blog campaign 'From Waste to Delicacy'. The study identifies four bundles of practices organising temporality: scheduling, pausing, stretching and synchronising. Within these bundles of practices, potential food waste is enacted differently: as not realised food waste, revitalised food, refuted food waste and harmonised food (waste). The study produces novel understanding about temporal inter-relations between humans and non-humans – the dance of agency – in household food waste reduction.